Implementing the principle of gender equality in a balance of secularism and religiosity - Saifnazarov Ismаil; Mukhtarov, Azamat; Ernazarov, Dilmurod; Mirakbarova, Dildora (Linguistics and Culture Review, 2021)
The article notes that the issue of gender equality in Uzbekistan has become a priority of public policy, especially the creation of an equal legal framework for the activities of women in all areas. But unfortunately, our people do not use them widely or are not allowed by their relatives. The gaps in our legal consciousness, in our spirituality, are clearly visible in the problem of gender equality. Gender equality is sometimes seen as the opposite of our national and religious values. To what extent do Islamic morality conform to the principle of gender equality, including whether there are equal opportunities for Muslims and non-Muslims in matters of education, and what is the status of gender equality in Muslim families? issues such as whether it is supported are covered in the scientific article on the basis of clear arguments.